Citizen Weiner [videorecording (DVD)] - Weiner, Zack; Weiner, Zack; Gallagher, Joe; Gallagher, Joe; Coffey, Sarah (Gravitas Ventures, 2024)
When the film industry shuts down, actor Zack Weiner and his friend Joe embark on a unique project: to make a film about running for city council, while actually running for New York's city council.